Serial Echocardiographic Follow-up of Structural Heart Interventions Performed During Pacific Partnership Interventional Cardiology Subject Matter Exchanges From 2015 to 2017 in Da Nang, Vietnam. (25th January 2021) - Nayak, Keshav R; Trieu, Nguyen Ba; O'Dell, Jeffrey; Kendall, Shellie; Stanton, Kelly; Thanh Han, Nguyen Huu; Krause, David; Wessman, Dylan; Lopez, Joseph; Phi-Lee, Trong; Adams, David; Parrish, J Scott; et al.
ABSTRACT: Introduction: The U.S. Navy Medicine has a long history of conducting global health missions that foster international diplomacy through medical knowledge exchange with a goal of increasing partner nation's health care capacity. Pacific Partnership is an annual U.S. Navy-sponsored joint operation that enhances medical collaboration with participating nations throughout the Indo-Asia-Pacific region. Since 2015, a U.S. Navy Cardiology team has conducted a structural heart disease interventional workshop focused on congenital heart disease with the cardiologists at the Da Nang General Hospital, Da Nang, Vietnam. Herein, we describe the multinational collaborative project including the patient registry we developed to monitor the short- and long-term outcomes of structural heart disease interventions preformed during Pacific Partnership 2015 and 2016. Materials and Methods: Our team developed a sustainable procedural registry with the goal of following the long-term outcomes of cardiac interventions for congenital heart disease in Vietnamese patients. Specifically, the registry was designed to record the changes in symptoms referable to the cardiovascular system and for device placement–associated complications for devices placed in 2015 and 2016 and has been updated annually thereafter. Results: Twelve patients (age range, 7 months to 31 years) underwent successful atrial septal defect closure in 2015 without procedural complications. The follow-up rate was 75% at 1 year and 67% at 2 years, and all devices were in appropriate position with no complications identified. Fifteen patients (age range, 20-66 years) underwent successful atrial septal defect closure in 2016. The follow-up rate was 62.5% at 1 year, and all devices were in appropriate position with no complications identified. Three patients (age range, 5-25 months) underwent successful device closure of the patent ductus arteriosus in 2015 without complications. The follow-up rate was 67% in 2016 and again in 2017. Six patients (age range, 9-74 years) underwent successful patent ductus arteriosus closure in 2016 without complications. The follow-up rate was 67% in 2017, and all devices were in appropriate position with no device-related complications identified. Conclusions: The development of a patient registry during these missions allowed for the longitudinal monitoring of outcomes for cardiac interventions. Notably, treated patients experienced symptomatic improvement without significant long-term procedural complications. Following patients longitudinally across medical missions is of recognized importance but remains a difficult objective to achieve for a multitude of factors including administrative and financial burdens on both the medical systems and the patients of host nations. Despite these limitations, longitudinal follow-up of patient care facilitated by a patient registry has a vital role in monitoring the quality of care provided and should be an integral part of all future global medical missions.